Robotic-assisted surgery in benign gynecology: single-center experience with 106 patients - Oujjat, Leïla; Rothmund, Ralf; Aghayev, Emin; Tsaousidis, Christos; Mueller, Martin (Frontiers in Medicine, 2025)
ObjectiveRobotic-assisted surgery is increasingly used in gynecology, offering technological and ergonomic benefits that overcome the limitations of traditional laparoscopy. This retrospective study evaluates perioperative outcomes, learning curve, and feasibility of robotic-assisted surgery for benign gynecological indications using the Da Vinci Xi Surgical System (Intuitive Surgical) at the Department of Gynecology and Obstetrics at Frauenzentrum Bern, Lindenhofspital AG, Switzerland.MethodsBetween August 2021 and November 2024, 106 consecutive patients underwent robotic-assisted surgery for various benign gynecological conditions. Clinical and perioperative outcomes were assessed. To evaluate the learning curve, the cohort was divided chronologically into two equal groups (first 53 and subsequent 53 cases). Differences between groups were analysed using multivariate logistic regression. The impact of potential predictors on total operation time was assessed using multivariate linear regression (significance level: p < 0.05). Predictors included: age, body mass index (BMI), uterine weight, parity, previous surgery, console time, operation time, conversion rate, blood transfusions, number of incisions, and patient group.ResultsAll cases were successfully completed robotically without conversion to laparotomy. No serious adverse events occurred. Logistic regression showed significant differences between the two groups in a 0.008-times heavier uterine weight (Confidence Intervals (CI) 0.003–0.014; p = 0.003), a 0.11-times higher BMI (CI 0.01–0.21; p = 0.032), a 0.06-times shorter console time (CI 0.01–0.10; p = 0.010), and a 1.91-times lower number of incisions (CI 0.43–3.39; p = 0.011) in the second group. Operation time did not differ significantly (p = 0.76). Linear regression showed that uterine weight and console time (both p < 0.001) were associated with operation time. Operation time increased by 7.6 (CI 5.2–9.9) minutes per 100 g of uterine weight, and by 7.8 (CI 5.5–9.8) minutes per 10 additional minutes of console time.ConclusionRobotic-assisted surgery is a safe and feasible alternative to conventional laparoscopy in benign gynecology. The learning curve was demonstrated by reduced console time and fewer incisions in later cases, despite higher BMI and uterine weight. Further studies should assess patient benefits and cost-effectiveness compared to conventional laparoscopy.